2021
DOI: 10.1021/acs.inorgchem.1c02232
|View full text |Cite
|
Sign up to set email alerts
|

M←NCCH3, M-η2-(NC)–CH3, and CN–M–CH3 Prepared by Reactions of Ce, Sm, Eu, and Lu Atoms with Acetonitrile: Matrix Infrared Spectra and Theoretical Calculations

Abstract: The reactions of laser-ablated Ce, Sm, Eu, and Lu atoms with acetonitrile were studied by matrix infrared spectra in a neon matrix, and M← NCCH 3 , M-η 2 -(NC)−CH 3 , and CN−M−CH 3 were identified with isotopic substitution and quantum chemical calculations. The major product is the insertion complex (CN−M−CH 3 ), while the end-on and side-on complexes (M←NCCH 3 and M-η 2 -(NC)−CH 3 ) are also trapped in the matrix. The CCN antisymmetric stretching mode for Ce-η 2 -(NC)−CH 3 was observed at 1536.9 cm −1 , whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
(108 reference statements)
1
3
0
Order By: Relevance
“…The bands at 1082.3, 1020.8 and 1068.7 cm −1 for 12 C, D and 13 C isotopes are in good agreement with the calculated results of N−Be stretching mode at 1106.0 ( 12 C), 1043.4 (D) and 1091.5 cm −1 ( 13 C), respectively. The absorption observed at 831.4 cm −1 with a 13 C isotopic substitution at 811.6 cm −1 lays in the region expected for a C−C stretching vibration, [ 37 ] and the large 12 C/ 13 C ratio of 1.0244 was obtained to verify our assignment. The corresponding D isotopic absorption was covered by the precursor bands.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The bands at 1082.3, 1020.8 and 1068.7 cm −1 for 12 C, D and 13 C isotopes are in good agreement with the calculated results of N−Be stretching mode at 1106.0 ( 12 C), 1043.4 (D) and 1091.5 cm −1 ( 13 C), respectively. The absorption observed at 831.4 cm −1 with a 13 C isotopic substitution at 811.6 cm −1 lays in the region expected for a C−C stretching vibration, [ 37 ] and the large 12 C/ 13 C ratio of 1.0244 was obtained to verify our assignment. The corresponding D isotopic absorption was covered by the precursor bands.…”
Section: Resultssupporting
confidence: 84%
“…The optimized structures of diberyllium and mono beryllium end-on and insertion complexes are shown in Figure 3 , with the end-on products in C s symmetry and the insertion complexes possessing C 3v symmetry. The point groups of beryllium products happen to be reverse with the C 3v point groups of N-coordination transition-metal complexes and C s structures of transition-metal insertion complexes (except for Mn products) [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. According to the NBO analysis in Table S8 , the electropositive beryllium forms sp hybrid orbitals, which make σ bonds with sp hybrid orbitals on the C atoms in the insertion complexes.…”
Section: Molecular Structures and Bondingmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of La-based endohedral metallofullerenes (EMFs), the La 4f-orbitals are found to play a critical role in the chemical reactivity and structure of the EMFs, with the La 4f-orbitals becoming more important as the size of the carbon cage is reduced . Reactions between Ce and acetonitrile studied by matrix infrared spectroscopy in neon matrices and density functional theory calculations reveal that the 4f-orbitals of Ce become active and participate in the bonding between Ce and C and N in Ce-η 2 -(NC)–CH 3 π-complexes . In addition to the brief overview of the literature above, there is a plethora of other recent examples where 4f-orbitals have been found to play an important role in lanthanide-containing compounds. It is of current interest to add to this developing field by probing small Ln containing molecules, like the diatomic lanthanide carbides, to further investigate the contributions of the 4f orbitals to the chemical bond.…”
Section: Introductionmentioning
confidence: 99%